Por fin es Carnaval - Dorros, Arthur; Dorros, Sandra Maurlanda (New York : Dutton Children's Books, 1991)
A family in South America eagerly prepares for the excitement of Carnaval.
Translation of: Tonight is Carnaval.
Keywords: Carnival -- South America -- Juvenile fiction